Ijtihad Tidak Bisa Membatalkan Ijtihad yang Lain - Muhammad Syarif (2021)
When ijtihad has gained legitimacy, will the legal product achieved through the ijtihad process be annulled by another ijtihad, or more easily can ijtihad be